The optimal tax treatment of housing capital in the neoclassical growth model - Essi Eerola; Niku Määttänen (Bank of Finland, 2005)
In a dynamic setting, housing is both an asset and a consumption good.But should it be taxed like other forms of consumption or like other forms of saving?We consider the optimal taxation of the imputed rent from owner housing within a version of the neoclassical growth model.We find that the optimal tax rate on the imputed rent is quite sensitive to the constraints imposed on the other available tax rates.In general, it is not optimal to tax the imputed rent at the same rate as the business capital income.
URN:NBN:fi:bof-20140807509
Keywords: H21; E21; 330; housing; capital taxation; optimal taxation